Polymerase chain reaction in detecting Leishmania sp in symptomatic and asymptomatic seropositive dogs - Soares, M. J. V. [UNESP]; Moraes, J. R. E. [UNESP]; Roselino, A. M. F. (Centro de Estudos de Venenos e Animais Peçonhentos, 2005)
In human and canine renal histological studies of visceral leishmaniasis (VL), the etiological agent is rarely found in situ. The objective of this study was to evaluate PCR in identifying the etiological agent in spleen, liver, lymph node, and kidneys of VL-seropositive dogs. Twenty-five symptomatic (case group) and 15 asymptomatic (control group) VL-seropositive dogs of different breeds, sexes, and ages from Teresina, Piauí State, Brazil, were used. Serologic diagnosis was made by enzyme-linked immunosorbent assay and indirect immunofluorescence test. Animals were subjected to euthanasia and necropsy. Renal fragments were immersed in buffered formaldehyde solution. Spleen, liver, lymph node, and kidney samples were collected and frozen at -70ºC until DNA extraction. After dehydration and diaphanization, renal fragments were infiltrated and embedded in paraffin, cut at 3 µm, and stained with hematoxylin-eosin (HE). DNA amplification used an automatic thermocycler with specific Leishmania primers. All case-group dogs and 2 controls showed positive results in spleen, liver, or lymph node PCRs. There was a significant difference by Fisher exact test. In symptomatic seropositive dogs, renal histopathological evaluation showed one animal (4%) with amastigote forms of Leishmania in inflammatory infiltrate, and kidney PCRs detected Leishmania DNA in eight animals (32%). The conclusion was that PCR is more precise than the conventional histopathology in detecting the Leishmania parasite in kidney.
Keywords: dogs; Leishmania; PCR; kidney